Azadirachta indica triterpenoids promote osteoblast differentiation and mineralization in vitro and in vivo. Issue 15 (1st August 2016) - Kushwaha, Priyanka; Khedgikar, Vikram; Haldar, Saikat; Gautam, Jyoti; Mulani, Fayaj A.; Thulasiram, Hirekodathakallu V.; Trivedi, Ritu
Graphical abstract: Schematic diagram outlining the novel triterpenoids isolated from Azadirachta indica by chromatographic techniques, have osteogenic activity. Out of eight compounds, only three compounds Azadirone, Azadirachtin A and Azadirachtin B have osteoblast proliferation, differentiation and mineralization ability. Azadirachtin A is most promising molecule which enhances gene expression and bone formation in vivo. Abstract: Terpenoids were isolated using chromatographic purification through solvent purification technique and identified as Azadirone (1 ), Epoxyazadiradione (2 ) Azadiradione (3 ) Gedunin (4 ) Nimbin (5 ) Salannin (6 ) Azadirachtin A (7 ) and Azadirachtin B (8 ) from Azadirachta indica . Out of eight compounds, only three compounds had osteogenic activity and enhanced osteoblast proliferation, differentiation and mineralization in osteoblast cells. Active compounds stimulated osteogenic genes ALP, RunX-2 and OCN expressions in vitro, but Azadirachtin A had a maximum ability to stimulate osteoblast differentiation and mineralization compared to other two active compounds. For in vivo study, Azadirachtin A injected subcutaneously in pups, which enhanced osteogenic gene expressions and promoted bone formation rate significantly. Here, we conclude that active compounds of Azadirachta indica have osteogenic activity and Azadirachtin A has a beneficial effects on bone.